1998
DOI: 10.1093/ajcp/110.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric DNA Analysis with Cytokeratin Gating of Formalin-Fixed Deparaffinized Breast Cancer Nuclei

Abstract: A b s t r a c tThe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…These results are consistent with a prior study in which semiquantitative cytologic examinations showed significant percentages of epithelial cells within specimen mammography‐guided FNAs of benign and malignant lesions as well as normal tissue (3, 20). There have been several studies in which ploidy and SPP on CK + and CK − cells have been evaluated (16, 30, 31). Although our study clearly showed that some CK − events were aneuploid nuclei of tumor cells, and that these cells might have expressed CK had they been intact cells, this situation has not been presented or discussed in the reports we have reviewed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are consistent with a prior study in which semiquantitative cytologic examinations showed significant percentages of epithelial cells within specimen mammography‐guided FNAs of benign and malignant lesions as well as normal tissue (3, 20). There have been several studies in which ploidy and SPP on CK + and CK − cells have been evaluated (16, 30, 31). Although our study clearly showed that some CK − events were aneuploid nuclei of tumor cells, and that these cells might have expressed CK had they been intact cells, this situation has not been presented or discussed in the reports we have reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the first reports in the literature describing any type of flow cytometric cell immunophenotyping in both benign and malignant breast disease and normal breast tissue. Studies that have been reported have focused on cell proliferation markers (13, 14, 16, 17) and not tumor markers. Positivity or negativity for a specific immunophenotype may have added prognostic significance compared with the overall level of a single marker or combination of markers in a breast lesion sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although algorithms have been designed to minimize some of these problems (30), ensuring that a flow cytometry sample is composed exclusively of tumor cells is the best way to avoid artifacts that result from normal cell contamination. Staining the specimens with cytokeratin and using dual-label gating has been useful in at least confining the analysis to epithelial cells, resulting in better quality results (32); however, normal epithelial cells are still able to contaminate the analysis. A better method of ensuring that only the neoplastic cells are analyzed is needed.…”
mentioning
confidence: 99%